Seed-mediated Growth of Au Nanoplates on the Functionalized Reduced Graphene Oxide Films for Surface-enhanced Raman Scattering - Kim, Young-Kwan; Jang, Hongje; Kang, Kyungtae (대한화학회, 2017)
We developed a seed-mediated growth strategy for the synthesis of Au nanoplate on the pyrene ethyleneglycol amine (PEA) functionalized reduced graphene oxide (PEA-RGO) films. This process yielded 17.6% of Au nanoplates on the PEA-RGO films, and the synthesized Au nanoplate/PEA-RGO nanohybrid films showed high potential as a surface-enhanced Raman scattering (SERS) platform.